Development technique for deep drawing without blank holder to produce circular cup of brass alloy - Saleh, Ali Hassan; Ali, Ammer Khalaf (International Journal of Engineering and Technology, 2015)
Of this technique compared to the conventional deep drawing is that the circular cup can be carried out in single action press with limit In this paper a new mechanism for deep drawing was proposed to produce circular cup from thin plate without blank holder. In this technique the die assembly includes punch, die and die-punch. A 2D axisymmetric finite element model was built using DEFORM software. Effect of die geometry (half- cone angle) on maximum load, thickness distribution, strain distribution and effect of clearance ratio between punch and (die-punch) on the wrinkling of the cup were investigated. Three half-cone angles of die (15o, 30o and 45o) were used for forming sheet metal of brass (CuZn37) which had initial thickness of (1mm) at four clearance ratio (c/t) for die of 30o half-cone angle. Finite element model results showed good agreement with experimental results. Die of 30o half-cone angle with clearance ratio (c/t) of 0.9 gave the best product without wrinkling. The main advantage drawing ratio (LDR) of 1.86 and blank diameter to blank thickness ratio (d/t) < 86.